Hermeneutyka reformy według Josepha Ratzingera - ROWLAND, Tracey; CHABRAJSKA, Dorota (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2012)
Whereas Concilium authors such as Edward Schillebeeckx, OP, and Karl Rahner, SJ, tended to approach the documents of the Council with what Ratzinger called a “hermeneutic of rupture,” making every pre-Conciliar belief and practice questionable, the Communio authors such as Joseph Ratzinger, Henri de Lubac, SJ, and Hans Urs von Balthasar offered a “hermeneutic of reform.” In his Christmas Address to members of the Roman Curia in 2005, Pope Benedict XVI made explicit reference to the concept of a “hermeneutic of reform” to describe his preferred approach to interpreting the documents of the Second Vatican Council. A key feature of his hermeneutic (consistent with the approach of Blessed John Paul II) is a strong Trinitarian Christocentrism or tendency to read the Conciliar documents with a Christocentric accent. This is especially so of the most highly debated document of the Council, Gaudium et Spes.